The experiences of health committes of community participation in health information campaigns during the COVID-19 pandemic - James, Carryn (Department of Public Health and Family Medicine, 2024)
Background: During the COVID-19 pandemic, a need arose for information to be provided to communities in a way that is understandable, practical and suited to their context, in order to empower communities to mobilize and actively participate in prevention measures against COVID-19.The People's Health Movement (PHM) in South Africa generated information pamphlets meant for dissemination and training among vulnerable communities, in efforts to facilitate knowledge translation about non-pharmacological prevention behaviours in the fight against the pandemic. It was not clear what benefit health information delivered in this way would have on the agency of bodies such as health committees, in taking ownership of advocating for the implementation of non-pharmacological behaviours, though similar theories could be formed from the study of previous pandemics. This study aimed to explore the perceptions health committee members have regarding the potential impact of health information relating to COVID-19 non-pharmacological prevention behaviours, and the ability of these modalities to facilitate community participation and agency in health. Methods: A qualitative approach was taken, and health committee members from the Khayelitsha and Klipfontein health districts were invited to participate in two rounds of focus groups. Data was analysed through thematic analysis. Member checking with participants was done throughout both focus groups Results: Five overarching themes were identified, that showed that knowledge translation and sense-making of non-pharmocological behaviours detailed by the PHM information pamphlets were impacted by elements unrelated to the content and structure of the resources itself. Discussion: The study highlighted the important role of multi-modal and multi-player participation in empowering bodies such as health committees to foster the agency of their people, in making sense of health information. The study highlighted the need for congruent and equitable interventions and information dissemination, that is acutely aware of the challenges faced by health committees in related to health information itself. A neglect of these challenges proves to negate even the most accurate and evidence based health information resource, as was seen in the health committees perception of the PHM information pamphlets. Future research could serve to explore broader perceptions of community participation in health information campaigns, to further account for the unique challenges faced by communities